Enhancing sexual education for children with special needs through augmented reality: development and evaluation of the Magical SeDu application - Maria, Eny; Satria, Bagus; Andrea, Reza; Imron, Imron; Karim, Syafei; Ramadhani, Fajar; Suswanto, Suswanto; Putra, Emil Riza; Sjamsir, Hasbi (International Journal of Electrical and Computer Engineering (IJECE), 2026)
This research focuses on the educational obstacles encountered by children with special needs (CWSN), specifically in sexual education, through developing and evaluating the Magical SeDu application. Using a three-phase instructional design model, the study followed the planning, design, and development phases to create user-centered features that meet diverse learning needs. User acceptance testing (UAT) further confirmed the usability and effectiveness of the app, with a satisfaction rating of 86.04%. These findings underscore the transformative potential of augmented reality (AR) technology in inclusive education, fostering interactive and visually stimulating learning experiences. The study also emphasizes the importance of involving stakeholders in the development process to ensure the app meets the specific needs of its users. Future research should focus on enhancing the app’s features and exploring its integration into broader educational environments to maintain accessibility and continuous improvement. This study contributes to the advancement of inclusive education strategies and highlights the critical role of sex education in increasing self-awareness and protection for children with special needs.